Epilepsy care: Work, upbringing, leisure, and Chinese culture - Tan, Chong Tin; Lim, Chooi Kwa (ASEAN Neurological Association, 2019)
Stigma in epilepsy arises from the misconceptions and prejudices rooted in the patient’s culture and traditions. Upbringing also has an important impact on the quality of life of epilepsy patients. In Chinese tradition, the main purpose of life is to be a “gentleman”, to fully express the true human nature. The essence of being a gentleman is “benevolence” and “virtue”. According to Zhuangzi’s concept of “virtue overcoming deformity”, virtue can prevail over physical deficiencies. Consistent with such a principle, a person with epilepsy should receive high honour if he can demonstrate the character of a “gentleman”. In - traditional Chinese culture, the sense of shame is the foundation of morality; “feeling shame” and “being shameless” are important moral concepts. A gentleman has a sense of shame, whereas a “petty person” is shameless. However, the ability to resist feeling inappropriate shame - “not feeling ashamed” is also a trait of the gentleman. Thus, based on traditional Chinese philosophy, one should resist feeling ashamed for having epilepsy. Chinese culture emphasizes the importance of exerting vitality in the presence of adversity; people with epilepsy who do not feel ashamed of their deficiency is manifesting such a vitality. Traditional Chinese culture takes a positive attitude towards hardship and adversity, that it is essential for developing character and skills. Overcoming adversity requires responsibilities, the pre-requisite is personal freedom. Thus, allowing freedom and nurturing independence is consistent with traditional Chinese attitude to upbringing. © 2019, ASEAN Neurological Association. All rights reserved.